G27(P) A bit about me: improving patient-centered care in paediatric intensive care units. (May 2019) - Stewart, CE; Vijayakumar, B; Spazzapan, M
Abstract : Aim: To assess whether the introduction of a board for non-medical information in each bedspace on the Paediatric Intensive Care Unit (PICU) can help provide health care professionals (HCPs) with a better insight into what those they care for are like as children not just patients, thereby improving patient-centred care. Method: The 'A Bit About Me' boards were created following a series of design consultations with staff, parents and patients. Chosen headings included on the boards were: 'Please call me…', 'Words to describe me', 'Important people to me', 'What makes me feel better when I'm upset' and 'Things you should know about me'. There was also a space for a favourite photograph or piece of artwork. HCPs and parents of children in PICU at St Mary's Hospital in London completed a seven-part questionnaire quantitatively assessing on a scale of 1–10 how well HCPs knew their patients before and after introducing the boards. Different versions of the questionnaire were created for parents and each healthcare specialty involved in patient care. Results: 38 and 36 questionnaires were collected pre- and post-intervention respectively. Unpaired t tests were used to analyse the results. Statistically significant improvements (p<0.005) were recorded in five of the items assessed (table 1 ). Qualitative feedback about the boards has been positive and recognised in thank you letters from families. Conclusion: Patient-centred care in PICU can be promoted by using boards in bedspaces where parents and children can share non-medical information about who they are and what they like. By helping HCPs know their patients better as children – their personality, comforters, important figures, fears and preferences – they can personalise their care accordingly and better appreciate what their baseline is. This is a simple, cost effective and sustainable intervention, which can lead to valuable improvements in family experiences.